Fake. Written by Floy Quintos. Directed by Tony Mabesa. UP Playwright’s Theatre. (May 7-15, 2011 at Teatro Hermogenes Ylagan, Bulwagang Rizal Faculty Center Bldg., University of the Philippines, Diliman, Quezon City, Philippines.) - Reilly, Brandon (Social Science Diliman: A Philippine Journal of Society and Change, 2011)
None
Keywords: None